Emigration and Regime Stability: Explaining the Persistence of Cuban Socialism - Bert Hoffmann (German Institute of Global and Area Studies (GIGA), 2005)
The 'Cuban safety-valve theory' explains sustained survival of Cuban socialism in part through the high levels of emigration, following Hirschman's model of 'exit' undermining 'voice'. The article argues that this remains insufficient in two important ways. Taking a closer look at the crisis years since 1989, at least as important as the opening of exit options was the Cuban state's capacity to rein in uncontrolled emigration and to reassure its 'gatekeeper role'. In addition, the transnationalization of voice and exit must be taken into account as a crucial factor, as much in feeding the regime's anti-imperialist discourse as, paradoxically, by generating sustained economic support from the emigrants.
Keywords: D31; H5; O15; 300; Emigration; Regime Stability; Transnational Networks; Cuba; USA